Reinstatement of Alysicarpus pokleanus (Leguminosae, Papilionoideae: Desmodieae) based on ITS sequences of nuclear ribosomal DNA - Kasana, Shruti; Dwivedi, Mayank D.; Pandey, Arun K. (Phytotaxa, 2021)
In the present communication, we evaluated the taxonomic status of Alysicarpus pokleanus Gholami & Pandey using nrDNA ITS sequences. Molecular and morphological diagnosis are provided which suggest reinstatement of A. pokleanus from the synonymy of A. hamosus.